DNMT3A facilitates breast cancer progression via regulating ADAMTS8 mediated EGFR-MEK-ERK activation - Shan Yang; Meng Cheng; Shaonan Zhang; Haoqi Wang; Jiaxing Wang; Xi Zhang; Yunzhe Mi; Sainan Li (PLoS ONE, 2025)
ADAMTS8 inactivation by epigenetic modifications has been reported in various tumors, and the dysregulation of ADAMTS8 expression is associated with poor clinical outcomes, cancer cell invasion, and metastasis. De novo methylation, involving DNMT3A, plays an important role in cancer development; however, it remains unclear whether DNMT3A regulates the progressive expression of breast cancer by regulating ADAMTS8. Through published cancer-related datasets and clinical validation, we found that ADAMTS8 and DNMT3A expression negatively correlated in breast cancer, and both associated with patient prognosis. Related cell experiments have shown that DNMT3A overexpression promotes breast cancer cell proliferation, migration, invasion, and apoptosis, whereas silencing DNMT3A has the opposite effect. Through Co-IP experiments, we confirmed that DNMT3A binds directly to ADAMTS8. Methylation-specific PCR (MSP) experiments confirmed that DNMT3A mediates ADAMTS8 promoter methylation in breast cancer. In addition, DNMT3A activated the EGFR-MEK-ERK signaling pathway by effectively downregulating ADAMTS8, whereas silencing ADAMTS8 effectively inhibited this signaling pathway. Taken together, our findings suggest that DNMT3A activates the EGFR-MEK-ERK signaling pathway by silencing ADAMTS8 transcription through methylation, thereby promoting breast cancer development. Therefore, DNMT3A may serve as an inhibitory target in breast cancer-targeted therapy.